Combination of Alarm-intervention and Reboxetine in Therapy- Resistant Enuresis - Kosilov, Kirill; Kuzina, Irina; Gainullina, Yuliya; Kuznetsov, Vladimir; Kosilova, Liliya; Karashchuk, Elena Viktorovna; Prokofyeva, Alexandra; Loparev, Sergay (Journal of Nepal Paediatric Society, 2018)
Introduction: The first-line treatments of primary monosymptomatic night enuresis (PMNE) are alarm intervention and desmopressin. Some patients are resistant to these modes of treatment. Therefore Reboxetine has been used to treat PMNE in these scenarios in recent years and published in many studies. The aim of the study was to determine effectiveness and safety of combination of Alarm intervention and Reboxetine, to treat patients with therapyresistant enuresis. Material and Methods: Two hundred and nineteen children of both sexes were participated in the experiment (average age, 11.3 years). Participants were divided into three groups: Group A (71 patients, Alarm intervention), Group B (79 patients, Reboxetine as monotherapy), Group C (69 patients, Alarm intervention + Reboxetine). The duration of treatment was twelve weeks, followed by follow-up period of twelve weeks to see efficacy. Result: There was no significant change in number of enuresis episodes per week before and after treatment in a group B. The number of enuresis episodes per a week (weekly) in a group C reached: before treatment 5.3 (1.5), after treatment 1.0 (0.8), 3 three months after the end of treatment 0.7 (0.7). The percentage of patients with PMNE in a group C was significantly less immediately after the course of treatment (17.4%), and three months after treatment (24.6%). Conclusion: Combined treatment of therapy-resistant enuresis with use of Alarm Intervention and Reboxetine gives a high percentage of cured patients both immediately after therapy (82.6%) and three months after the end (75.4%).